The chemical speciation of zinc in human saliva: possible correlation with reduction of the symptoms of the common cold produced by zinc gluconate-containing lozenges - Bakar, N.K.A.; Taylor, D.M.; Williams, D.R. (1999)
This work attempts to correlate the effectiveness of treatment with zinc gluconate lozenges in reducing the symptoms of common colds as measured in seven double-blind clinical trials in 648 volunteers, with (1)the total amount of zinc gluconate administered and (2) the salivary concentration of specific zinc species. The speciation was assessed using the JESS computer simulation of speciation in our saliva model. The results show that there is a significant correlation between the biological response and the concentration of free Zn-aq(2+), ions in saliva at pH 5.5. (P congruent to 0.01) or pH 6.75 (P < 0.05), whereas there is no obvious correlation between biological response and the total amount of zinc present following the dissolution of a zinc gluconate lozenge in the mouth. The results suggest that optimal activity requires salivary free Zn-aq(2+), ion concentrations of >4 and >8 mmol dm(-3) for saliva at pH = 6.75 and pH = 5.5, respectively.